Pengaruh Penambahan Serat Limbah Plastik HDPE terhadap Kuat Tekan pada Mortar - Yoga Aprianto Harsoyo; Muhammad Rifqi Fauzi (Bulletin of Civil Engineering, 2021)
Mortar is a construction material commonly used in building and road infrastructure. Some constructions that use mortar include Lane Concrete (LC), species, light brick adhesives, wall plaster, mechanical installation, and others. HDPE plastic waste fiber (High density polyethylene) in this study is a mixture of materials as binders and cement substitutes. HDPE plastic is one type of plastic that when viewed visually is classified as concentrated, where the use of this type of plastic is usually used for beverage bottles. The HDPE plastic type is easy to recycle. In 2015, global plastic waste in the world was recorded at 2.5 billion tons per year, so this research is expected to reduce the amount of plastic waste in Indonesia. The purpose of this study was to analyze the effect of mixing HDPE plastic waste fibers on compressive strength and mortar weight. This HDPE variations of 0%, 2%, 4%, and 6% is used from the weight of the cement. This study was carried out to obtain the compressive strength at the ages of 7 days and 28 days using cube specimens with dimensions of 15 cm × 15 cm × 15 cm. Based on the results of the test, the highest compressive strength for mortar at of 2% fiber variation at 28 days is 14.47 MPa. The compressive strength of mortar at the age of 7 and 28 consecutive days increased by 11%. While the addition of fibers, compressive strength of mortar decreases with the increasing number of fiber mixtures. Fiber mortar decreased in weight from 7696 grams to 7640 grams, 7422 grams, and 7280 grams, for fiber of 2%, 4%, and 6% respectively.